Open days: The public presentation of schools - Feito Alonso, Rafael; Rujas Martínez-Novillo, Javier; Sánchez Rojo, Alberto (Education Policy Analysis Archives, 2021)
This paper deals with the way schools –state schools and public-funded private ones– present themselves to their potential users in open days. It draws on qualitative fieldwork based on participant observation conducted in such events in 31 schools of Madrid. In these events, schools mobilize their material, human, and symbolic resources to produce an appealing school image, even though differences arise depending on the kind of school (public, private), the courses offered, and the social composition of the neighborhood. Public-funded private schools have in general more attractive buildings and facilities, an interest in recruiting pupils in every stage, and show a greater investment of resources and efforts than state schools to build a school image. This allows them to craft an apparently more coherent and solid narrative than state schools, where pupils spend less years, there is greater teacher mobility and a lack of educational marketing professional counselling. In open days, schools communicate explicit messages and implicit impressions, and reveal the image they want to display as well as the one they wish to avoid. These events are part of school’s strategies in a competitive school market, while at the same time they entail an exposure to the public eye as they can be judged and compared.